1989
DOI: 10.1007/bf01849356
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum IUD contraception — a review of an international experience

Abstract: Postpartum insertion of intrauterine contraceptive devices (IUDs) performed while women are still in hospital has a number of advantages. Earlier reports, however, generally associated this procedure with high expulsion rates. Recent studies, on the other hand, have shown that if IUDs are inserted immediately (within 10 minutes) after placental delivery, it is safe and effective. In some experienced centers, fairly low expulsion rates are reported. In this paper the experiences with postplacental IUD insertion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
4

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 39 publications
0
29
0
4
Order By: Relevance
“…5 Also, postpartum IUCD insertion is not associated with an increased risk of infection, uterine perforation, postpartum bleeding or uterine subinvolution. 6 This study was conducted to evaluate the safety and efficacy of immediate postpartum intrauterine contraceptive device (PPIUCD) insertion in women delivering vaginally or by cesarean section.…”
Section: Introductionmentioning
confidence: 99%
“…5 Also, postpartum IUCD insertion is not associated with an increased risk of infection, uterine perforation, postpartum bleeding or uterine subinvolution. 6 This study was conducted to evaluate the safety and efficacy of immediate postpartum intrauterine contraceptive device (PPIUCD) insertion in women delivering vaginally or by cesarean section.…”
Section: Introductionmentioning
confidence: 99%
“…The expulsion rates in trials of immediate post-partum insertion generally appear lower than those reported with delayed post-partum insertions. 21 After clinical examination, the position of the IUCD was in situ in 97.61% of subjects.…”
mentioning
confidence: 99%
“…810 Postplacental insertion has an expulsion rate ranging from 6% to 20% for T-shaped IUDs over 1 year. 1114 The expulsion rate is lower for immediate postplacental compared with early (11 minutes to 72 hours) postpartum insertion and is also lower when skilled health care providers insert the IUD. 11,12 The method of postpartum insertion, whether inserted by ring forceps or by hand, does not appear to affect expulsions.…”
mentioning
confidence: 99%